Effective Interventions for Enhancing Academic Achievement in Higher Education: Views of Entrepreneurship Students - Lucky Sibanda; Chux Gervase Iwu (University Babes-Bolyai, 2023)
Entrepreneurship is considered a vehicle for fighting unemployment in developing countries such as South Africa. As a result, research focusing on entrepreneurship education continues to gain traction. Graduates of tertiary institutions are expected to contribute meaningfully either through employment or job creation. This expectation puts the role of tertiary institutions in converting students into graduates in the spotlight. Tertiary institutions deal with many challenges, such as the heterogeneity of the student population, which calls for evidence-based interventions that are tailor-made to the needs of specific cohorts. Thus, various stakeholders should support tertiary institutions by helping them achieve the desired graduate attributes. This paper sought to suggest effective interventions that would enhance the academic success of entrepreneurship students and prepare them to become future job creators. Interventions should capitalize on students' strengths and improve on their weaknesses. The researchers argue that interventions to promote academic success should consider students' abilities and drive to complete qualifications, lecturers' teaching methods, and graduate attributes required by society. The study used a quantitative approach to address the research question and collected data from 204 undergraduate entrepreneurship students at a technology university in South Africa. The study suggests effective interventions from descriptive statistics. This study reveals the importance of understanding students' backgrounds, entrepreneurial attributes and teaching methods when designing academic interventions. Implications to the academic administrators and lecturers as well as recommendations for future studies are flagged.